Analisis Strategi Promosi untuk Meningkatkan Wisatawan Mancanegara pada Museum Bustanil Arifin PDIKM Padang Panjang - Liddia Nursita Sari; Dewi Anggraini (Lembaga Yasin AlSys, 2026)
Museum Bustanil Arifin PDIKM Padang Panjang is a cultural tourism destination in West Sumatra with considerable potential to attract international tourists through the richness of Minangkabau history and culture. However, the number of international tourist visits continues to fluctuate, necessitating more effective and sustainable promotional strategies. This study aims to analyze the promotional strategies implemented by Museum Bustanil Arifin PDIKM Padang Panjang to increase international tourist visits. This study employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation and were subsequently analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that the museum has implemented five elements of the promotional mix, namely advertising, personal selling, sales promotion, public relations, and direct marketing. Nevertheless, their implementation has not been optimal because digital promotion has not been conducted consistently, partnerships with travel agents and influencers have not been established, and the use of foreign languages in promotional media remains limited. Advertising through social media, particularly Instagram, is the most effective strategy for attracting international tourists because it serves as their primary source of information before deciding to visit. This study concludes that increasing international tourist visits requires consistent digital promotion, expanded strategic partnerships, and the provision of multilingual promotional media. These findings provide practical implications for museum management in developing more integrated promotional strategies to expand international market reach and enhance the appeal of Minangkabau cultural tourism.